2011
DOI: 10.3928/15428877-20110627-08
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Optical Coherence Tomography in Intraoperative Ophthalmic Imaging

Abstract: Optical coherence tomography (OCT) has transformed diagnostic ophthalmic imaging but until recently has been limited to the clinic setting. The development of spectral-domain OCT (SD-OCT), with its improved speed and resolution, along with the development of a handheld OCT scanner, enabled portable imaging of patients unable to sit in a conventional tabletop scanner. This handheld SD-OCT unit has proven useful in examinations under anesthesia and, more recently, in intraoperative imaging of preoperative and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 55 publications
0
39
0
4
Order By: Relevance
“…External OCT has limitations in that metallic surgical instruments cast dense optical shadows upon the underlying tissues of interest [27][28][29]31]. In addition, a major limitation is the ability to efficiently locate and follow the surgical instrument as the membrane peeling or other procedure occurs [27][28][29]. Finally, optical aberrations of the media will reduce clarity of the externally acquired OCT image [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…External OCT has limitations in that metallic surgical instruments cast dense optical shadows upon the underlying tissues of interest [27][28][29]31]. In addition, a major limitation is the ability to efficiently locate and follow the surgical instrument as the membrane peeling or other procedure occurs [27][28][29]. Finally, optical aberrations of the media will reduce clarity of the externally acquired OCT image [5].…”
Section: Discussionmentioning
confidence: 99%
“…The value of OCT imaging in the ophthalmic operating room has been demonstrated with an external system in evaluating the changes of the retinal structures immediately following surgical manipulation [27][28][29][30][31][32][33]. This would ensure that the intended procedure has been completed as desired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][11][12][13][14][15][16][17][18][21][22][23]27,28,[32][33][34][35][36][37][38][39][40][41] The PIONEER study was a large prospective clinical study (n = 531) examining the role of intraoperative OCT with a microscope-mounted portable OCT system in ophthalmic surgery. 13 The DISCOVER study is a subsequent prospective clinical study (n = 227) examining microscope-integrated OCT in ophthalmic surgery.…”
Section: Clinical Use and Impactmentioning
confidence: 99%
“…Intraoperative OCT (iOCT) has recently been introduced by several research groups, [1][2][3][4] and has been reported to be useful in vitreoretinal, [5][6][7][8] anterior segment, [9][10][11] and glaucoma surgery. 12 In Europe and in the United States, microscopeintegrated iOCT units are commercially available from two different manufacturers.…”
Section: Introductionmentioning
confidence: 99%